PENILAIAN TINGKAT TEKNOLOGI DOK PEMBINAAN UPT BTPI MUARA ANGKE JAKARTA - Achmad Fauzan; Yopi Novita; Vita Rumanti Kurniawati (Institut Pertanian Bogor, 2009)
This article determines about technology level Dok Pembinaan Unit Pelaksana Teknis Balai Teknologi Penangkapan Ikan (UPT BTPI) Muara Angke, Jakarta. Assessment of technology level is conducted by using model technometric to calculate TCC (technology contribution coefficient) value from technology component, consist of: technoware (hardware), humanware (human resources), inforware (information component), and orgaware (organization component). Value of component contribution orgaware haves contribution is lower value as 0.347, whereas component humanware haves highest contribution as 0.600. TCC value from Dok Pembinaan UPT BTPI Mua-ra Angke as 0.447 indicate that technology in that shipyard has been fair and can be told that level of shipyard technology is semi modern.Key word: shipyard, technology, technometric model